Diagrid structures for tall buildings: case studies and design considerations. (23rd July 2012) - Mele, Elena; Toreno, Maurizio; Brandonisio, Giuseppe; De Luca, Antonello
SUMMARY The originality of form is one of the new trends that can be identified in the current design of tall buildings. In this design trend, the so‐called diagrid structures, which represent the latest mutation of tubular structures, play a major role due to their inherent esthetic quality, structural efficiency and geometrical versatility. In this paper, an overview on application of such typology to high‐rise buildings is carried out; in particular, in the first part of the paper, the peculiarities of diagrid systems are described: starting from the analysis of the internal forces arising in the single diagrid module due to vertical and horizontal loads, the resisting mechanism of diagrid buildings under gravity and wind loads is described, and recent researches and studies dealing with the effect of geometry on the structural behavior are discussed. In the second part of the paper, a comparative analysis of the structural performance of some recent diagrid tall buildings, characterized by different number of stories and different geometries, namely the Swiss Re building in London, the Hearst Headquarters in New York and the West Tower in Guangzhou, is carried out, and some general design remarks are derived. Copyright © 2012 John Wiley & Sons, Ltd.